Pelaksanaan Eksekusi Jaminan Fidusia dalam Hal Debitur Wanprestasi Pada Koperasi Simpan Pinjam Wisata Bali - I Wayan Wahyu Wisnanta; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Preferensi Hukum, 2020)
Cooperatives hold a very positive role in the improvement of people’s welfare in Indonesia, so that the welfare of the wider community can be enhanced significantly. Cooperatives perform a crucial task to improve the standard of living of all members of society. In carrying out its duties, the cooperative also acts as a financial place that has the purpose of providing loans and other money service needs. This study examines the implementation of the fiduciary guarantee execution and the factors that hinder the implementation of the said fiduciary guarantee if the debtor defaults at the Bali Tourism Cooperative. This research was conducted using empirical legal research. The data source of this research is primary data, which is data obtained from research carried out directly in the field and from cooperatives. The results show that the implementation of fiduciary security at the Bali Tourism Savings and Loans Cooperative is in accordance with the Standard Operating Procedures (SOP) owned by the Bali Tourism Savings and Loan Cooperative and does not conflict with existing regulations. Factors hampering the execution of the fiduciary guarantees in the event of defaulting debtors are guarantees that they are not registered at a fiduciary institution due to cost and time. Therefore, in issuing credit with a fiduciary guarantee, the Bali Tourism Cooperative must make an authentic deed before a notary and be registered with the Ministry of Law and Human Rights in order to further ensure legal certainty for negligence in the obligation to treat fiduciary collateral as the responsibility of the fiduciary debtor.